2009
DOI: 10.1097/tp.0b013e3181919f5d
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Pretransplant Serum CXCL10 for Cardiac Acute Rejection

Abstract: In HTx recipients, measurement of pretransplant CXCL10 serum levels could be a clinically useful tool for predicting cardiac acute rejection, especially in the early posttransplant period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
(33 reference statements)
0
32
0
Order By: Relevance
“…and CXCL11 (19). CXCL10, a factor determined to have the highest predictive value for early cardiac acute rejection (20), was initially reported to be induced by IFN-γ and secreted by various cell types, including monocytes, neutrophils, endothelial cells, keratinocytes and fibroblasts (21,22). After the first transplantation, CXCL10 was released into the circulation and recognized by CXCR3, which was expressed on the surface of Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…and CXCL11 (19). CXCL10, a factor determined to have the highest predictive value for early cardiac acute rejection (20), was initially reported to be induced by IFN-γ and secreted by various cell types, including monocytes, neutrophils, endothelial cells, keratinocytes and fibroblasts (21,22). After the first transplantation, CXCL10 was released into the circulation and recognized by CXCR3, which was expressed on the surface of Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CXCL10 in human leishmaniasis is not clear, although CXCL10 is well-known for its involvement in recruiting monocytes, M⌽s, T cells, and NK cells (29) during human viral and bacterial infections (18,26) and organ transplantation (8). By using a murine model of L. amazonensis infection, our group has previously shown that exogenous CXCL10 promotes parasite killing in M⌽ cultures in vitro (40) and enhances the antigen-presenting function in infected DCs (41) and that local injection of CXCL10 significantly delays the onset of cutaneous lesions (40).…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence that CXCR3 and its ligands (CXCL9, CXCL10 and CXCL4) are implicated in the pathogenesis of transplant rejection [34,36,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]106]. For example, an increase in the concentration of CXCR3 ligands and the infiltration of CXCR3+ T cells has been demonstrated in biopsies from rejected solid organ transplants, including lungs [44], kidneys [107], skin [54] and endomyocardial tissue [46].…”
Section: The Role Of Cxcr3 In Transplant Rejectionmentioning
confidence: 99%
“…However, the binding of platelet-derived CXCR3 ligands induces angiostasis [34,93]. Due to the pleiotropic nature of CXCR3, the involvement of this receptor has been described in inflammatory, autoimmune and angiogenesis-related disorders such as inflammatory arthritis [94][95][96][97], systemic sclerosis [97][98][99][100], type I diabetes [97,101,102], transplant rejection [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and cancer [36,38,[103][104][105].…”
Section: Cxcr3 Functions and Its Ligandsmentioning
confidence: 99%
See 1 more Smart Citation